RESULTS OF CATCHING CRABS (Scylla Sp) WITH MANY BAITS USING PINTO FISHING GEAR ( LIFT NET) - Jefri Sahat; Nofrizal '; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractThe research about results of catching crabs (Scylla Sp) with many baits using pinto fishing gear ( lift net) was do in september 2014 at desa sei nagalawan, Kecamatan Perbaungan, Kabupaten Serdang Bedagai SumateraUtara. Aims to compare result of catching crabs use bait, commonly used by fisherman with another bait alternative. Will be expected can increase fisherman income. The method used in this research is experimetall fishing method is trials catching crabs (Scilla Sp) use natural bait an semi artifial bait with used lift net fishing techniques. Was done in 10 repetition and 4 treatments in one day was doing 2 times catches . research was doing in three days.The results of research show total most result of cacthing are used head of chicken bait ( 82 crabs) second, with used fish bait (43 crabs) last, with belangkas bait (33 crabs) and the most low results is with mixed bait (19 crabs).Keywords: Pento Fishing gear, bait, crab